Pengaruh penerapan LKS virtual laboratory dalam model generative learning terhadap pencapaian kompetensi siswa pada materi kinematika kelas X SMA Adabiah Padang - mutia faizah apriani; masril masril; yenni darvina; hidayati hidayati (PILLAR OF PHYSICS EDUCATION, 2019)
The purpose of this study was to determine the effect of applying the virtual laboratory LKS in the generative learning model on the achievement of the competency of students in class X senior high school Adabiah in Padang. The experimental class uses LKS virtual laboratories while the control class uses LKS provided by the school. These competencies include competency in attitude, knowledge and skills . Competence of attitude assessed continued for four indicators which tolerance, cooperation, honesty and discipline. Assessment of the attitude competence assessment using the observation sheet which was conducted for eight meetings. Based on the results of the analysis of the observation sheet, student’s attitudes showed that the attitude of the experimental class students was better than the control class, where the average score of the experimental class attitudes was 87,75 and the control class was 83,75. Knowledge competency seen from posttest and skill competency is known based on the results of performance assessment during practicum. Based on the results of the analysis it was stated that the relationship of achievement of knowledge competencies with the application of virtual laboratory LKS was strong with a series coefficient of 27,8%. While the coefficient of determination of the skills competency relationship and application of the virtual laboratory LKS was 20,8% Keywords : Virtual Laboratory LKS, Competency, Generative Learning